Narrativas de reportagens policiais em Gurupi – TO: uma análise das reportagens sobre ações da polícia militar exibidas no programa Sil TV Notícias - Correia, Clifton Morais (2022)
This study aims to show reports that have the direct involvement of the Tocantins military police in the city of Gurupi. Arrests, arrests, confrontations of suspects with the PM are shown, as well as actions of military sniffer dogs. All reports are from the Sil TV Notícias program, shown from Monday to Friday, from 12:00 to 13:00 on channel 19 da Band. The materials analyzed are from the official fanpage of the broadcaster and data collection took place between January and April 2021. This research was called bibliographical, as it provided theoretical support on the profession of journalists, the media and the language used in journalistic and also documentary vehicles, as it presents an analysis of material that has not yet been analyzed. In the results found, a partial journalistic production was noticed, with little concern with care in textual construction, in addition, the primary concepts of construction of a report, which is always listening to more than one side of the story, were not obeyed. As an example, as collected in the research, in terms of titles, of the 30 narratives analyzed, 22 start talking directly about the action of the military police or of the sniffer dogs that belong to the military police. This clearly shows that the objective of the report is to give greater emphasis to the actions taken by the military police in the city of Gurupi.